The Influence of Work-Life Balance, Organizational Culture, and Job Satisfaction on Employee Performance at PT. GMF AeroAsia Tbk (Case Study on the Aircraft Support and Industrial Solution Unit) - Saputra, Wawan; Rosihana, Athiy Dina; Madewi, Astuti; Kharisma, Megania (Journal of Economics and Social Sciences (JESS), 2025)
Since employee performance directly impacts productivity and the achievement of corporate objectives, it is a critical factor in organizational success and competitiveness. Thus, the purpose of this study is to investigate how job happiness, organizational culture, and work-life balance affect the preservation and enhancement of employee performance. Quantitative approaches were used in this investigation. Saturated sampling was used throughout the sample process, yielding 93 responders. Primary data for this investigation were collected through questionnaires. To analyze the data, multiple linear regression was employed. The findings suggest that job happiness, corporate culture, and work-life balance all partially and concurrently affect worker performance.